The Effect of New Pattern of Level IV Leadership Training and Education Policy Implementation on Leadership Competence of Supervisory Officials in Gorontalo Provincial Government - Irfan Ibrahim (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
The effectiveness of government administration is very dependent on the government official leadership quality. Therefore, leaders in government organizations must have high qualifications, competencies and performance in order to achieve organizational goals. Implementation of the New Pattern of Diklatpim IV Policy is expected to increase the Supervisory Official Leadership Competence. This study aims to determine how much influence the implementation of the New Pattern Diklatpim IV policy on leadership competencies of supervisory officials in the Gorontalo Provincial Government. The research method uses quantitative design with an explanatory survey method. Data collection uses questionnaire techniques distributed to 84 respondents by stratified random sampling from 520 of population. Data analysis using Partial Least Square (PLS) was processed using SmartPLS 3.1 software to test the measurement model and find out the significance of the influence of the New Pattern of Diklatpim IV Policy Implementation on Supervisory Leadership Competencies. The results showed that the Implementation of the New Pattern of Diklatpim IV Policy on Supervisory Officials Leadership Competencies had a significant effect.